2020
DOI: 10.1007/s00382-020-05332-0
|View full text |Cite|
|
Sign up to set email alerts
|

Model uncertainties in climate change impacts on Sahel precipitation in ensembles of CMIP5 and CMIP6 simulations

Abstract: The impact of climate change on Sahel precipitation suffers from large uncertainties and is strongly model-dependent. In this study, we analyse sources of inter-model spread in Sahel precipitation change by decomposing precipitation into its dynamic and thermodynamic terms, using a large set of climate model simulations. Results highlight that model uncertainty is mostly related to the response of the atmospheric circulation to climate change (dynamic changes), while thermodynamic changes are less uncertain am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
85
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 74 publications
11
85
1
Order By: Relevance
“…Over the western Sahel, monsoon precipitation tends to move southward. Although at a weaker intensity, similar changes have been obtained at a near-term time horizon (i.e., over the period 2010-2049) (Monerie et al, 2017) and with the RCP4.5 emission scenario (Monerie et al 2012;Akinsanola and Zhou 2018), and the CMIP6 Shared Socioeconomic Pathways (Almazroui et al 2020;Monerie et al 2020).…”
Section: Sahel Precipitation Forced Response To Global Warmingsupporting
confidence: 66%
See 1 more Smart Citation
“…Over the western Sahel, monsoon precipitation tends to move southward. Although at a weaker intensity, similar changes have been obtained at a near-term time horizon (i.e., over the period 2010-2049) (Monerie et al, 2017) and with the RCP4.5 emission scenario (Monerie et al 2012;Akinsanola and Zhou 2018), and the CMIP6 Shared Socioeconomic Pathways (Almazroui et al 2020;Monerie et al 2020).…”
Section: Sahel Precipitation Forced Response To Global Warmingsupporting
confidence: 66%
“…Fontaine et al (2011b) have shown that a robust pattern emerges over the Sahel in response to global warming, with the majority of CMIP3 climate projections showing an increase in central Sahel precipitation and a decrease in western Sahel precipitation. This has also been shown within the CMIP5 ensemble (Monerie et al 2012(Monerie et al , 2013(Monerie et al , 2016Biasutti 2013;Roehrig et al 2013;James et al 2015;Diallo et al 2016;Gaetani et al 2017;Akinsanola and Zhou 2018;Dunning et al 2018) and the CMIP6 ensemble (Almazroui et al 2020;Monerie et al 2020). The multi-model ensemble also projects a modulation of the seasonal cycle of Sahel precipitation, with a decrease over the western Sahel occurring mainly during the early Sahel rainy season (i.e., May-June-July-August) and an increase over the central Sahel occurring mainly during the last months of the Sahel rainy season (i.e., August-September-October) (Biasutti 2013;Seth et al 2013;Monerie et al 2016;Dunning et al 2018).…”
Section: Introductionsupporting
confidence: 63%
“…The projected enhancement of the GM precipitation amount has been attributed to the combination of two opposing effects between the weakened monsoon circulation due to stabilization of the atmosphere and the increase of atmospheric moisture content due to atmospheric warming (Hsu et al, 2012; Lee & Wang, 2014). The changes in spatial pattern of monsoon precipitation has been attributed to the shifts of tropical circulation (Chadwick et al, 2013; Held & Soden, 2006; Monerie et al, 2020; Rowell & Chadwick, 2018). Wang et al (2020) pointed out that two greenhouse gas (GHG)‐induced thermodynamic effects, i.e., the increase of specific humidity and the increase of atmospheric stability due to top‐heavy heating, tend to offset each other; on the other hand, the GHG‐induced horizontally differential warming results in the robust “NH‐warmer‐than‐SH” and “land‐warmer‐than‐ocean” patterns, as well as an “El Niño–like warming” pattern, driving circulation change (the GHG‐induced dynamic effect) that plays a fundamental role in shaping the spatial patterns of the GM precipitation changes.…”
Section: Introductionmentioning
confidence: 99%
“…The increases in monsoon precipitation, however, have substantial intermodel spread (Hsu et al, 2013; Jayasankar et al, 2015; Kitoh et al, 2013; Monerie et al, 2016, 2020; Park et al, 2015; Rowell & Chadwick, 2018). It has been argued that the considerable uncertainty of GM precipitation may be influenced by different global warming rates among the CMIP5 models (Hsu et al, 2013; Oueslati et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation